Relatório técnico-científico e-burguer: sistema de customização de lanche - FIDELIS, Kalil Francisco Braz; LIMA FILHO, Matheus Rodrigo Queiroz de (106, 2021)
FIDELIS, Kalil Francisco Braz, LIMA FILHO, Matheus Rodrigo Queiroz de. E-BURGUER: Sistema de customização de lanche. Guaratinguetá, 2021. 21 páginas. Relatório Técnicocientífico, Curso de Análise e Desenvolvimento de Sistemas, Faculdade de Tecnologia de Guaratinguetá, 2021.For many years, the hamburger has been considered a passion by its consumers. The snack that conquered the world after the First World War, won mainly on Brazilians' dishes. Research finds that due to a pandemic of COVID19, they had an exponential increase. Due to the difficulty of going out to bars or snack bars, the hamburger played a prominent role in this scenario and a significant increase in applications and delivery deliveries. Most of the time when you are going to consume a snack at a burger place, it is common to find a professional who is unprepared to take the order, often causing the order to be delivered with errors. Based on this perception, the objective is to develop a web / mobile system where the user can create their snack from scratch or order and modify their snack, promoted through a menu, so that the order is correctly noted and so that there is no confusion in the assembly time, in addition to order management by the establishment. It is expected that from the management and use of the system, the errors in annotations will decrease and generate a snack bar for the loyalty of its customers.
Keywords: Web sites; Lanchonetes; Informação e Comunicação